2022
DOI: 10.7717/peerj.14129
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between illness perception, pain intensity and quality of life in elderly with low back pain in Denmark: a cross-sectional study

Abstract: Background Illness perception is related to management patterns and pain intensity, but among elderly with low back pain, this relation is unclear. The aims of this study were to analyse the associations between illness perception, pain intensity and health related quality of life in a group of elderly with low back pain and explore how different illness perception profiles would cluster and differ in terms of pain, quality of life and choice of management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Based on the results from other studies [ 38 , 39 ], we initially anticipated that being female would be a risk factor. However, no significant associations were found in the adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results from other studies [ 38 , 39 ], we initially anticipated that being female would be a risk factor. However, no significant associations were found in the adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
“…HRQoL is impacted by chronic BP in different domains of life, such as physical and mental well-being, social relationships, and functional capacity [ 23 ]. In a recent study, greater pain intensity was associated with the perception of BP as a greater threat and lower HRQoL [ 35 ]; the more pain participants experienced, the worse their HRQoL [ 36 ].. A comparison between individuals who reported BP and matched pain-free controls indicated that older adults people with BP reported significantly impaired HRQoL scores and a significantly lower self-assessment of general health [ 37 ]. In the present study, participants from both countries had an impact of the intensity of BP on their HRQoL, but the intensity of pain reflected on HRQoL was lower in Brazilian older adults.…”
Section: Discussionmentioning
confidence: 99%
“…HRQoL is impacted by chronic BP in different domains of life, such as physical and mental well-being, social relationships, and functional capacity [21]. In a recent study, greater pain intensity was associated with the perception of BP as a greater threat and lower HRQoL [32]; the more pain participants experienced, the worse their HRQoL. [33].…”
Section: Back Pain and Hrqolmentioning
confidence: 99%